Analysis of Shear Stress and Rutting Performance of Semirigid Base Asphalt Pavement on Steep Longitudinal Slope - Jiafu Guo; Song Yang; Yongchao Sun; Zhensheng Chao; Ruikang Yang; Huailei Cheng (Advances in Civil Engineering)
Rutting is the most common distress of the asphalt pavement with a semirigid base, mainly when located on a steep longitudinal slope. Previous studies have shown that shear stress is the leading cause of rutting. Therefore, it is essential to analyze the distribution characteristics of shear stress to evaluate pavement rutting performance. Firstly, the truck speed was measured at different locations on the steep longitudinal slope section. Then, the calculation method of shear stress was improved based on the method of “systematic clustering.” The distribution characteristics of shear stress were studied under the different gradients, slope lengths, horizontal forces, and interlayer bond conditions. Finally, the rutting prediction model was used to evaluate the rutting performance of the steep longitudinal slope section. The results show two critical parameters of a steep longitudinal slope: gradient and slope length can be quantified by establishing the relationship between truck speed and those parameters. The improved shear stress calculation method can correspond well with the layer where maximum rutting occurs. Gradients and slope lengths have little effect on shear stresses, while horizontal forces and interlayer bond conditions significantly change the shear stress distribution characteristics within the pavement. For the steep longitudinal slope sections, the rutting prediction model should consider the truck speed separately. With increasing gradient and slope length, the rutting increases the fastest in the middle layer. For sections with horizontal forces and poor interlayer bonding, the layers with the highest rutting accumulation are the upper layer and the lower layer, respectively.